Labor Income, Relative Wealth Concerns, and the Cross Section of Stock Returns - Gómez, Juan-Pedro; Priestley, Richard; Zapatero, Fernando (Journal of Financial and Quantitative Analysis, 2016)
The finance literature documents a relation between labor income and the cross section of stock returns. One possible explanation for this is the hedging decisions of investors with relative wealth concerns. This implies a negative risk premium associated with stock returns correlated with local undiversifiable wealth because investors are willing to pay more for stocks that help their hedging goals. We find evidence that is consistent with these regularities. In addition, we show that the effect varies across geographic areas depending on the size and variability of undiversifiable wealth, proxied by labor income.